Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1126/sciadv.abp9005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting OXPHOS de novo purine synthesis as the nexus of FLT3 inhibitor–mediated synergistic antileukemic actions

Abstract: Using a genome-wide CRISPR screen, we identified CDK9 , DHODH , and PRMT5 as synthetic lethal partners with gilteritinib treatment in fms-like tyrosine kinase 3 ( FLT3 )–internal tandem duplication (ITD) acute myeloid leukemia (AML) and genetically and pharmacologically validated their roles in gilteritinib sensitivity. The presence of FLT3 -ITD is associated with an increase in anaerobic gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A previous report using CRISPR/Cas9 screening suggested synergy between DHODH and FLT3 inhibition (32). Using these same CRISPR/Cas9 data, another study demonstrated that a switch from glycolysis to oxidative phosphorylation may represent a metabolic adaptation that could mediate gilteritinib (gilt) resistance (33). Therefore, we investigated the synergy between HOSU-53 and gilt using a modified, more aggressive MOLM-13 model in which treatment started 10 days postengraftment (versus 4 days in all other MOLM-13 CDX studies).…”
Section: Introductionmentioning
confidence: 77%
“…A previous report using CRISPR/Cas9 screening suggested synergy between DHODH and FLT3 inhibition (32). Using these same CRISPR/Cas9 data, another study demonstrated that a switch from glycolysis to oxidative phosphorylation may represent a metabolic adaptation that could mediate gilteritinib (gilt) resistance (33). Therefore, we investigated the synergy between HOSU-53 and gilt using a modified, more aggressive MOLM-13 model in which treatment started 10 days postengraftment (versus 4 days in all other MOLM-13 CDX studies).…”
Section: Introductionmentioning
confidence: 77%
“…Notably, previous work done in AML cell lines that show resistance to chemotherapy also show increased mitochondrial mass and increased OxPhos. 56 …”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy-resistant AML cells displayed a high oxidative phosphorylation status . Targeting mitochondrial protein synthesis and electron transfer induced an energetic shift toward low OXPHOS and markedly enhanced antileukemic effects of chemotherapy. HsClpP chemo-activation by ONC201 or ONC212 has been proven as a promising approach that can be used against AML. , However, the antileukemic effects of ONC201 or ONC212 monotherapy is limited in AML. , It seems that more efficient HsClpP agonists can better elucidate the therapeutic value of targeting HsClpP in AML. Thus, a novel class of HsClpP agonists is designed and synthesized using a ring open strategy based on the lead compound 1 , which is designed through a position shift strategy based on the imipridone ONC201 .…”
Section: Discussionmentioning
confidence: 99%